FASCIOLIASIS IN CATTLE- A REVIEW - M. A. A. Rana; N. Roohi; M. A. Khan (Journal of Animal and Plant Sciences, 2014)
Fascioliasis is a common disease of cattle and other ruminants caused by F. hepatica and F. gigantica. The disease is world wide in distribution and is liable for causing extensive economic losses to the livestock industry encompassing reductions in weight gain, milk yield and fertility. In this study knowledge about prevalence, diagnosis, treatment and control of Fascioliasis has been reviewed. This article evaluates more recent work along with previous studies. The fecal egg count, signs / symptoms and specific antibodies in serum were the only diagnostic tools in the past however now for detection of F. hepatica specific copro-antigen has been developed and commercialized. An indirect enzyme linked immunosorbent, assay (IEA) allows an early diagnosis. The tracer animals and snail studies have widened the existing knowledge. The treatment has been carried out mainly with Fasciolicides (Albendazole, Oxyclozanide and Triclabendazole), however resistance has been developed. Most of the recommended treatments are not feasible. Seasonal deworming is essential. Pasture management by creating bio competent environment with snail predators can be very effective in reducing the rate of incidence and controlling the problem. Vaccine is there but is not frequently used due to incompatible immune response. The studies on reduction in milk yield due to Fascioliasis are still lacking and require extensive research/ investigations.
Keywords: Fascioliasis; F. hepatica; F. gigantica; Snails; Cirrhosis